Nilai Karakter Tanggung Jawab dalam Novel Hati Suhita (2019) Karya Khilma Anis - Gita Surya Minasti; Nurul Yakin; Muhammad Fahrurrozi; Asriati Aulia Malik (Haluan Sastra Budaya, 2025)
The character of responsibility is an attitude and behavior in carrying out one's duties and obligations, which should be fulfilled towards oneself, society, the environment, the state, and God. Responsible behavior can be shaped through education and habits. The values of responsibility are not only obtained from formal educational institutions but can also be learned from literary works filled with moral values. One such work is the novel Hati Suhita by Khilma Anis.This research is qualitative with a library research approach. The primary data source is the novel Hati Suhita by Khilma Anis, while the secondary data obtained from books, journals, and articles related to the character values of responsibility. The data analysis technique used is content analysis, which involves examining the values of responsibility in the novel.The results of the study reveal that Hati Suhita presents nine values of responsibility, including: choosing the right path, constantly improving oneself, maintaining one’s honor, being vigilant, committing to one's duties, performing tasks with high standards, acknowledging one’s actions, keeping promises, and having the courage to face the consequences of one's actions and words.